تأثير تقانة التطعيم على أصول مقاومة في إنتاج ونمو ومكونات ثمار طعوم بعض أصناف البندورة المزروعة في البيت البلاستيكي - الشعبي صلاح; قطيفاني أسامة; صافية محمد; أسمر جورج (Latakia University Journal -Biological Sciences Series, 2019)
تم إجراء البحث في الهيئة العامة للبحوث العلمية الزراعية بدمشق (عملية تطعيم والتئام وتقسية نباتات البندورة)، وفي محطة الجماسة التابعة لمركز البحوث العلمية الزراعية في محافظة طرطوس، وفي أرض المزارع في منطقة الخراب (ريف بانياس) خلال المدة ما بين 2003 – 2005. هدف هذا البحث إلى دراسة تأثير بعض أصول البندورة (إلدورادو، هيمان، فايجوماكس، بيوفورت) المقاومة للاجهادات الأحيائية المتسببة عن آفة نيماتودا تعقد الجذور ومرض الجذر الفليني تحت ظروف العدوى الطبيعية في البيت البلاستيكي إضافة للأصل المحلي الحساس إزاءها في إنتاج ونمو ومكونات ثمار بعض أصناف البندورة (جيروندا، ديما/ستيلا، أمل، والمحلي) المطعمة عليها مقارنة بنباتات الأصناف نفسها غير المطعمة. بينت النتائج أن الأصول الأربعة للبندورة؛ إلدورادو، هيمان، فايجوماكس، وبيوفورت قد أثرت إيجاباً في الإنتاج الثمري للنباتات المطعمة ونموها بدرجات متباينة، وبلغت معدلات الزيادة في الإنتاج الثمري 22.2، 18.5، 33.3، 24.4%، على التوالي، بينما بلغت معدلات الزيادة في متوسط طول النبات الواحد 7.5، 11.8، 2.1، 5.6%، على التوالي. ولم تؤثر الأصول المختبرة بصورة معنوية في مكونات ثمار البندورة المنتجة من نباتات مطعمة مقارنة بالثمار المنتجة من النباتات غير المطعمة باستثناء السكريات، فكانت المكون الأكثر تبدلاً. This study was carried out in the General Commission for Scientific Agricultural Research (GCSAR) in Damascus (grafting, healing and acclimatization processes of tomato plants), at the Jemaseh Station of the Scientific Agricultural Research Center in Tartous governorate, and in the farmer field of Al-Khrab region (Banias countryside) during 2003 – 2005. The study aimed to demonstrate the influence of some biotic stress- resistant tomato rootstocks (Eldorado, He-man, Vigomax, and Beaufort) caused by root-knot nematodes and corky root disease under natural infection conditions in plastic house in addition to the susceptible local (wild) tomato rootstock on the yield, growth, and fruit components of some tomato cultivars (Gironda, Dima/Stella, Amal, and local Landrace) grafted onto it, in comparison with the same non-grafted cultivars. Results showed that four rootstocks Eldorado, He-man, Vigomax and Beaufort, had positively influenced the fruit yield and growth of grafted plants with different levels. The increasing rates of fruit yield for rootstocks grafted with tested varieties were 22.2, 18.5, 33.3, and 24.4%, respectively; meanwhile, they were 7.5, 11.8, 2.1, and 5.6%, respectively, for the average length of grafted plants. The investigated rootstocks had not significantly affected the tomato fruit components of grafted plants compared with the non-grafted ones, with the exception of saccharides, as it was the most variable component.